Inclusion proposal of Santa Clara Community in the information society - Farias, Maria Giovanna Guedes; Freire, Isa Maria (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2011)
It presents a research work proposal, in development in the Masters Program in Information Science at the Universidade Federal da Paraíba (UFPB), which aims to intervene in the process of informational exclusion experienced by Santa Clara Community in the João Pessoa city, Paraíba state. This intervention will occur through field research for registration, organization and dissemination of “information sources”, constituted by people from the community. For that it will be produced a website where it will deposited, to free access in the internet, the “knowledge treasure” of people who form the social memory and knowledge of Santa Clara Community, that will be available for the next generations, which may facilitate the production of new knowledge by other social actors. link para o texto completo: http://www2.marilia.unesp.br/revistas/index.php/bjis/article/viewFile/286/277